ESPÉCIES DE ANUROS DO GÊNERO Dendropsophus COLETADAS NA REGIÃO CENTRO-SUL DO ESTADO DO PIAUÍ (AMPHIBIA, ANURA, HYLIDAE) - Miranda, Danilo Almeida de; Silva, Liliane Arrais da; Barbosa, Diogo Brunno e Silva; Lima, Mauro Sérgio Cruz Souza (Revista Nordestina de Zoologia, 2017)
Brazil currently has 1.039 species of anurans, divided into 20 families and 90 genera, the Hylidae family is composed of 690 species, distributed throughout the country, among which 64 of these species belong to the genus Dendropsophus. Starting from this point we seek to understand and know the distribution of the genus Dendropsophus in the mid-southern region of the state of Piauí. 5 species have already been described for the state of Piauí (D. soaresi, D. nanus, D. rubicundulus and D. minutus), in our field works we were able to find D. soaresi, D. nanus, D.rubicundulus and D. minutus, all in the mid-southern region of the state of Piauí. However, the distribution results of the Dendropsophus genus are incipient, requiring efforts to understand the diversity and distribution of the group.